Peroxiredoxin II Is Essential for Maintaining Stemness by Redox Regulation in Liver Cancer Cells. (25th February 2016) - Kwon, Taeho; Bak, Yesol; Park, Young-Ho; Jang, Gyu-Beom; Nam, Jeong-Seok; Yoo, Jeong Eun; Park, Young Nyun; Bak, In Seon; Kim, Jin-Man; Yoon, Do-Young; Yu, Dae-Yeul
Abstract: Redox regulation in cancer stem cells (CSCs) is viewed as a good target for cancer therapy because redox status plays an important role in cancer stem-cell maintenance. Here, we investigated the role of Peroxiredoxin II (Prx II), an antioxidant enzyme, in association with maintenance of liver CSCs. Our study demonstrates that Prx II overexpressed in liver cancer cells has high potential for self-renewal activity. Prx II expression significantly corelated with expression of epithelial-cell adhesion molecules (EpCAM) and cytokerain 19 in liver cancer tissues of hepatocellular carcinoma (HCC) patients. Downregulation of Prx II in Huh7 cells with treatment of siRNA reduced expression of EpCAM and CD133 as well as Sox2 in accordance with increased ROS and apoptosis, which were reversed in Huh7-hPrx II cells. Huh7-hPrx II cells exhibited strong sphere-formation activity compared with mock cells. Vascular endothelial growth factor (VEGF) exposure enhanced sphere formation, cell-surface expression of EpCAM and CD133, and pSTAT3 along with activation of VEGF receptor 2 in Huh7-hPrx II cells. The result also emerged in Huh7-H-ras G12V and SK-HEP-1-H-ras G12V cells with high-level expression of Prx II. Prx II was involved in regulation of VEGF driving cancer stem cells through VEGFR-2/STAT3 signaling to upregulate Bmi1 and Sox2. In addition, knockdown of Prx II in Huh7-H-ras G12V cells showed significant reduction in cell migration in vitro and in tumorigenic potential in vivo. Taken together, all the results demonstrated that Prx II plays a key role in the CSC self-renewal of HCC cells through redox regulation.